The escalating prevalence of Neologisms in modern English usage - Miramonova, Dilnura (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
This article provides an in-depth examination of neologisms and their linguistic importance. A neologism is generally defined as “a new word or expression, or a new meaning for an existing word”. The study explores how neologisms emerge, the linguistic processes by which they are formed, and their role in reflecting and influencing contemporary culture. Drawing on the works of prominent linguists –including David Crystal, Jean Aitchison, and Steven Pinker –the research outlines theoretical perspectives on language change and lexical innovation. The article explores how neologisms contribute to the language system by introducing terms for new ideas and phenomena, thereby enriching the vocabulary. It emphasizes the dynamic nature of language and how neologisms reflect ongoing social changes. Linguists view the emergence and adoption of neologisms as key indicators in language studies. The article highlights the significance of neologisms in linguistic research and their role in the evolution of language.